Kerf-Less Exfoliated Thin Silicon Wafer Prepared by Nickel Electrodeposition for Solar Cells - Yang, Hyun-Seock; Kim, Jiwon; Kim, Seil; Eom, Nu Si A.; Kang, Sangmuk; Han, Chang-Soon; Kim, Sung Hae; Lim, Donggun; Lee, Jung-Ho; Park, Sung Heum; Choi, Jin Woo; Lee, Chang-Lyoul; et al. (Frontiers in Chemistry, 2019)
Ultra-thin and large-area silicon wafers with thickness in the range of 20 to 70 μm were produced by spalling through the use of a nickel stressor layer. A new equation for predicting the thickness of the spalled silicon was derived from the Suo–Hutchinson mechanical model and the kinking mechanism. To confirm the reliability of the new equation, the proportional factor of the stress induced by nickel on the silicon wafer was calculated. The calculated proportional factor of λ = 0.99 indicates that the thickness of the spalled silicon wafer was proportional to that of the nickel layer. A similar relationship was observed in the experimental data obtained in this study. In addition, the thickness of the stressor layer was converted to a value of stress as guidance when using other deposition conditions and materials. A silicon wafer with predicted thickness of 50 μm was exfoliated for further analysis. In order to spall a large-area (150 × 150 mm2 or 6 × 6 in2) silicon wafer without kerf loss, initial cracks were formed by laser pretreatment at a proper depth (50 μm) inside the exfoliated silicon wafer, which reduced the area of edge slope (kerf loss) from 33 to 3 mm2. The variations in thickness of the spalled wafer remained under 4%. Moreover, we checked the probability of degradation of spalled wafers by using them to fabricate solar cells; the efficiency and ideality factor of the spalled silicon wafers were found to be 14.23% and 1.35, respectively.